Oncoplastic Volume Displacement Techniques for Breast Conserving Surgery in Patients with Breast Cancer - Hamdy Mohamed Hussein, Omar Farouk Ali, Mohammed Ahmed Omar, Hamdy Hamed Mousa, (Chelonian Research Foundation, 2024)
Breast cancer is the most common cancer in women, responsible for over 10% of new cancer cases annually and is the second leading cause of cancer death among women worldwide. The breast, consisting of 15-20 lobes and fat that determines size and shape, produces milk in response to hormones. Breast cancer often develops silently (Sathish Kumar, 2018), and is frequently detected through routine screenings or symptoms such as lumps, shape changes, or nipple discharge. Diagnosis requires physical exams, mammography, and biopsy, with early detection significantly improving survival. The cancer can spread via lymphatic and blood systems, leading to metastasis and a poor prognosis, underscoring the need for screening programs (Mahvi, et al. 2018).